2020
DOI: 10.1038/s41598-020-77566-1
|View full text |Cite
|
Sign up to set email alerts
|

Rate of misdiagnosis and clinical usefulness of the correct diagnosis in exudative neovascular maculopathy secondary to AMD versus pachychoroid disease

Abstract: The aim of this study was to explore the relative prevalence and clinical differences between age-related macular degeneration (AMD) and pachychoroid disease in patients older than 50 years with newly diagnosed exudative neovascular maculopathy, and also assess the rate of misdiagnosis between these two disorders. In this retrospective observational study, we reviewed data from patients 50 years of age and older with newly diagnosed treatment-naïve exudative macular neovascularization (MNV) secondary to AMD or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…This difference may be due to the fact that in this study we were better able to measure thicker choroids using SS-OCT 45 , 46 . It may also be due to the fact that in this study, we classified PNV separately, since some eyes that were previously classified as classic exudative AMD were classified as PNV 5 , 9 , 47 . Although CT was not used in the PNV diagnostic criteria in this study, it ay be due to the fact that PNV has a thicker CT than classic exudative AMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be due to the fact that in this study we were better able to measure thicker choroids using SS-OCT 45 , 46 . It may also be due to the fact that in this study, we classified PNV separately, since some eyes that were previously classified as classic exudative AMD were classified as PNV 5 , 9 , 47 . Although CT was not used in the PNV diagnostic criteria in this study, it ay be due to the fact that PNV has a thicker CT than classic exudative AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several diseases that share the characteristic of choroidal vessel engorgement or thickening 3 6 , are classified into pachychoroid spectrum diseases (PSDs). However, it is unclear whether the PCV and PNV are variants of AMD or a distinct disease entity 8 , and it is often difficult to differentiate PCV and PNV from typical neovascular AMD 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective analysis, Miyake et al 2 found that at least 20% of eyes diagnosed as having AMD before the advent of the “pachychoroid era”, should have been diagnosed as pMNVs instead. Similarly, in a recent study, Borrelli et al 12 reported that the pMNV prevalence in their study cohort was 25.2%. Most interestingly, 15.4% of pMNV patients had been misdiagnosed as AMD patients.…”
Section: Introductionmentioning
confidence: 56%
“…The pachychoroid phenotype predisposes to a spectrum of diseases including pachychoroid pigment epitheliopathy, central serous chorioretinopathy (CSC), pachychoroid neovasculopathy (PNV), polypoidal choroidal vasculopathy/aneurysmal type 1 neovascularization, focal choroidal excavation, peripapillary pachychoroid syndrome, and pachychoroid geographic atrophy 3 , 5 10 . Noteworthily, the occurrence or exudation of MNV may complicate all pachychoroid disorders (pMNV) 6 , 9 – 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Second, the definition of pachychoroid may be controversial. Borrelli et al 31 reported that15.4% of neovascular AMD subjects were re-evaluated as pachychoroid. We minimized the controversy by specifying the quantitative value of SFCT and exploring multimodal images by two graders in setting the ground truth.…”
Section: Discussionmentioning
confidence: 99%